2017
DOI: 10.1038/s41598-017-05895-9
|View full text |Cite
|
Sign up to set email alerts
|

Concise and Stereodivergent Synthesis of Carbasugars Reveals Unexpected Structure-Activity Relationship (SAR) of SGLT2 Inhibition

Abstract: Carbasugar sodium-glucose cotransporter 2 (SGLT2) inhibitors are highly promising drug candidates for the treatment of Type 2 diabetes mellitus (T2DM). However, the clinical usage of carbasugar SGLT2 inhibitors has been underexplored, due to the lengthy synthetic routes and the lack of structure-activity relationship (SAR) studies of these compounds. Herein, we report a concise and stereodivergent synthetic route towards some novel carbasugar SGLT2 inhibitors, featuring an underexploited, regioselective, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The basic difference is that canagliflozin has a thienyl moiety bridging the two phenyl rings of the pharmacophore aglycone, whereas dapagliflozin and empagliflozin have a methylene group instead ( Figure 1 ). The latter two also contain a chlorine substitution on their phenyl rings, whose electronegativity (i.e., “pulling” electron pairs from the aromatic π ring electron cloud) further protects against its metabolic degradation [ 6 ]. The chlorine atom also increases the inhibitory potency against SGLT2 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic difference is that canagliflozin has a thienyl moiety bridging the two phenyl rings of the pharmacophore aglycone, whereas dapagliflozin and empagliflozin have a methylene group instead ( Figure 1 ). The latter two also contain a chlorine substitution on their phenyl rings, whose electronegativity (i.e., “pulling” electron pairs from the aromatic π ring electron cloud) further protects against its metabolic degradation [ 6 ]. The chlorine atom also increases the inhibitory potency against SGLT2 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter two also contain a chlorine substitution on their phenyl rings, whose electronegativity (i.e., “pulling” electron pairs from the aromatic π ring electron cloud) further protects against its metabolic degradation [ 6 ]. The chlorine atom also increases the inhibitory potency against SGLT2 [ 5 , 6 ]. In contrast, canagliflozin has a fluorine substitution on one of its phenyl rings, which is also very electronegative and increases metabolic stability [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While recent studies have attempted to dock phlorizin-derived compounds into inward-facing models of hSGLTs 7 , the Wright lab has demonstrated that SGLT2 inhibitors bind from the extracellular solution likely stabilizing a Na + -bound, outward-facing conformation 8 . Thus, a detailed molecular view of this interaction is not possible without a reliable outward-facing model of SGLTs.…”
Section: Introductionmentioning
confidence: 99%
“…In the following four decades, the chemical, biological, and conformational aspects of carbasugars were extensively studied [12,13], resulting in studies on enzyme inhibition, lectin-binding, and even HIV and cancer treatment [14][15][16]. Various strategies have been employed for the synthesis and isolation of carbasugars, mostly starting from simple monosaccharides such as glucosamine and resulting in the corresponding carbasugars [17][18][19]. Other approaches work from simple hexopyranoses to more complex carbafuranoses such as carbaarabinofuranosides [20,21] or even more complex carbasugar derivatives such as fluorinated carbasugars [22].…”
Section: Introductionmentioning
confidence: 99%